The interrogation of an accused and its impact on the confession in the Islamic Jurisprudence in (Comparison to Secular Law) - Alsarahen, Hussien Hlayyel Suleiman (Journal of Islamic Sciences, 2021)
The study discusses the legality of the interrogation 0f the accused and its impact on the confession from the following aspects: the definition of the interrogation of the accused, the linguistic and contextual definition of the confession, and any related utterances. The study will also discuss the Eligibility and importance of the interrogation, principles of interrogation, and conditions of the accused. The researcher concluded that there is no benefit from the confession if it was by force furthermore, the impermissibility of torturing the accused in order to force the confession, unless the accused is known by their bad deeds. The researcher followed the descriptive method which relies on analyzing data and reading through details in order to conclude the results.